Staged Tendon Repair to Improve Range of Motion in Tamai Zone 4 Replantation: Two Case Reports - Matsusue, Takeo (Archives of Plastic Surgery, 2024)
Tamai zone 4 replantation, defined as the replantation at a level proximal to the flexor digitorum superficialis' insertion and distal to where the common digital artery branches into the proper digital artery, has poor functional results because making orthosis and rehabilitation protocols that protect the bone and the flexor and extensor tendons simultaneously difficult. Two cases of Tamai zone 4 replantation are presented: one case of an index finger replantation at the proximal phalanx and a case of ring finger replantation at the proximal interphalangeal joint. The author did not repair the flexor tendon intentionally in the primary replantation and performed two-stage flexor tendon reconstruction later. The total active motions (TAMs) at the last follow-up were 215 and 180 degrees, respectively, with the latter distal interphalangeal joint being an arthrodesis. Both cases had no extension lag in the proximal interphalangeal joint. These results were much better than those in previous reports, in which the mean TAM was 133 degrees or less. The good results appeared to be mainly due to the reasonable and clear postoperative rehabilitation protocols made by the proposed procedure. This procedure may be useful for obtaining reproducible functional results even in Tamai zone 4 replantation.
Keywords: replantation; range of motion; articular; rehabilitation; tendon; finger